Mathematical Problem-Solving Abilities in Algebraic Operations through Realistic Mathematics Education (RME) - Izzati Mauren Sefira; Ali Shodikin (Program Studi Tadris Matematika Universitas Islam Negeri (UIN) Salatiga, 2026)
This study aims to describe the mathematical problem-solving abilities of seventh-grade students in algebraic operations through the RME approach, focusing on two aspects, how the characteristics of RME support or constrain students’ problem-solving processes, and students’ problem-solving performance based on three of Polyas’ stages. Problem-solving abilities were analyzed using three of Polya’s stages, understanding the problem, devising a plan, and implementing the plan. The looking-back stage was excluded as this study focuses on processes explicitly documented in students’ written responses. This study employed a descriptive qualitative approach with 11 seventh-grade students as research subjects. Data were collected through written tests and interviews. The results of the study show that the indicator implementing a plan was the most frequently mentioned in students’ responses. The indicator understanding the problem and formulating a plan remained relatively low, most students did not fully list the given and asked information, nor did they explicitly state their problem-solving strategies. The use of real-world contexts in RME helps students understand problem situations, but it has not yet fully encouraged structured planning. These findings indicate the need to strengthen the early stages of problem-solving in RME instruction so that students can solve problems more systematically.